CHARACTERIZATION OF RICE MILLS OF BLACK TABAH WHICH IS IN THE COBALT-60 RAY RADIATION 300 Gray IN WILD LAND - CHANDRA AGROTEKNOLOGI 2014; Tantri palupi; Maulidi Maulidi (Fakultas Pertanian Universitas Tanjungpura, 2019)
Characterization of Steadfast Black Rice is an observation process that aims to find out and find characters. The purpose of this study was to determine morphological and agronomic characteristics of Tabah black rice rice mutants that had been radiation with Cobalt-60 300 Gray. This research was carried out in the rice field of the Main Seedling Center. Sui snapper. The results of observing the ability to reproduce (a little), stiffness of the stem (mostly arch), flair (0% = 3%), (1% = 14.4%), (2% = 12.6%), 3% = 7, 2%), plant height (short, 16.2%), (medium, 20.4%), (high, 3%), out of panic (SMKS, 3%), (SMKL, 4.8%), ( Vocational School, 28.2%), (MTK, 5.4%), hair loss (Easy), grain application (Fertil), plant age (152), seedling height (32.1cm), long leaves (short, 2, 4 %), (medium, 18.6%), (length, 14.4%), (very long 0.6%), leaf width (1.8 cm), leaf surface (medium), leaf angle (<45 ˚), corner of flag leaf (upright, 1.8%), (medium, 24%), (horizontal, 10.2%), leaf neck color (light green), white leaf color (white), leaf color of the book ( yellow gold 33%), (green 3%), color of leaf blade (dark green), color of leaf midrib (green), length of leaf tongue (1.1 cm, 6%), (1.2 cm 15.6%) , (1.3 cm 12%), (1.4 cm 2.4%), leaf tongue color (white), leaf tongue shape (2-gap), number of tillers (6), stem angle (medium), color stem segment (golden yellow), panicle length (26.7cm), ti ma ma lai (between medium 0.6%), (between medium and open, 4.2%), (open 31.2%) secondary panicle (small), panicle (straight), color of lemma and palea (Brown spots on setting 33%), (yellow, 3%), grain color (purple 33%), (yellow straw 3%), seeds long (long), long broken skin (long), weight 100 grains 2 grams).